Mechanim design and intentions - Felix Bierbrauer; Nick Netzer (University of Zurich, Department of Economics, 2012)
We introduce intention-based social preferences into a Bayesian mechanism design framework. We first show that, under common knowledge of social preferences, any tension between material efficiency, incentive compatibility, and voluntary participation can be resolved. Hence, famous impossibility results such as the one by Myerson and Satterthwaite (1983) are turned into possibility results. Second, we provide a systematic account of the welfare implications of kindness sensations. Finally, we turn to an environment without common knowledge of social preferences and introduce the notion of a psychologically robust mechanism. Such a mechanism can be implemented without information about the type or the intensity of social preferences. We show that the mechanisms which have been the focus of the conventional mechanism design literature can be modified to achieve psychological robustness.
Keywords: C70; C72; D02; D03; D82; D86; 330; Mechanism Design; Psychological Games; Social Preferences; Intentions; Reciprocity; Revelation Principle; Soziale Wohlfahrtsfunktion; Austauschtheorie (Soziologie); Nichtkooperatives Spiel; Asymmetrische Information; Mechanismus-Design-Theorie